2009
DOI: 10.1177/0034355209345161
|View full text |Cite
|
Sign up to set email alerts
|

Race-Ethnicity, Education, and Employment After Spinal Cord Injury

Abstract: The objective of this article was to identify the relationship between race-ethnicity and employment after spinal cord injury (SCI), while evaluating interrelationships with gender, injury severity, and education. The authors used a cohort design using the most current status from a post-injury interview from the National SCI Statistical Center. Participants included 14,454 adults ages 18 to 64, at least 1 year post-injury, not currently students or homemakers, and with residual impairment. Primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
3
26
1
Order By: Relevance
“…First, having the opportunity to return to pre-injury employer and employment were associated with almost 3 years (earlier) time difference with those who did not have this opportunity. This is similar to previous studies 6,9 that also found this path to work faster and therefore the recommendation that every effort be made by the rehabilitation team to work towards this goal if it is feasible. If this is not possible, the interval of time to work after SCI may be considerably longer.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…First, having the opportunity to return to pre-injury employer and employment were associated with almost 3 years (earlier) time difference with those who did not have this opportunity. This is similar to previous studies 6,9 that also found this path to work faster and therefore the recommendation that every effort be made by the rehabilitation team to work towards this goal if it is feasible. If this is not possible, the interval of time to work after SCI may be considerably longer.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the conclusion and recommendations of Krause et al, 6,9 whereby the focus should be on, how long is the window open for returning to the pre-injury employer or utilizing the pre-injury skills. Given the nature, longevity and compensation scheme of a particular job skill or occupation, allowing an individual time to adjust to his/her SCI as is the current practice may inadvertently contribute to closing the window of opportunity for a relatively speedy time to work.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations